Cultural Adaptation: The Resilience of Musicians Based on Artistic Creativity in Preserving Traditional Keroncong Music - Suryati, Suryati; Jamnongsarn, Surasak; Sanjaya, RM Singgih; Widodo, Tri Wahyu; Rokhani, Umilia (SCAD Independent, 2025)
Resilience based on artistic creativity by musicians has had positive implications for preserving Keroncong’s music. However, this context needs to be addressed in scientific discussions. In addition to complementing previous studies, this study focused on explaining the characteristics of resilience based on artistic creativity carried out by musicians in preserving Keroncong music. This study showed three significant findings. First, resilience based on artistic creativity carried out by musicians by composing made Keroncong music more inclusive and could be enjoyed by all groups. Second, resilience based on artistic creativity carried out by musicians by performing informal stage acts made Keroncong music an attractive genre. Third, resilience based on artistic creativity carried out by musicians by covering popular songs made the Keroncong genre became adaptive music. This study also recommends the importance of future studies that explain the resilience process of musicians in preserving Keroncong music by intensively interviewing musicians who consistently perform Keroncong songs.